Green tea supplementation increases glutathione and plasma antioxidant capacity in adults with the metabolic syndrome - Basu, Arpita (2013)
Green tea, a popular polyphenol-containing beverage, has been shown to alleviate clinical features of the metabolic syndrome. However, its effects in endogenous antioxidant biomarkers are not clearly understood. Thus, we tested the hypothesis that green tea supplementation will up-regulate antioxidant parameters (enzymatic and non-enzymatic) in adults with the metabolic syndrome. Thirty-five obese participants with the metabolic syndrome were randomly assigned to receive one of the following for 8 weeks: green tea (4 cups/day), control (4 cups water/day), or green tea extract (2 capsules and 4 cups water/day). Blood samples and dietary information were collected at baseline (0 week) and 8 weeks of the study. Circulating carotenoids (alpha-, beta-carotene, lycopene) and tocopherols (alpha-, gamma-tocopherols), and trace elements were measured using high performance liquid chromatography (HPLC) and inductively-coupled plasma mass spectroscopy (ICP-MS), respectively. Serum antioxidant enzymes (glutathione peroxidase, glutathione, catalase) and plasma antioxidant capacity were measured spectrophotometrically. Green tea beverage and green tea extract significantly increased plasma antioxidant capacity (1.5μmol/L to 2.3μmol/L and 1.2μmol/L to 2.5μmol/L respectively, p<0.05) and whole blood glutathione [1783 μg/g hemoglobin (Hb) to 2395 μg/g Hb and 1905 μg/g Hb to 2751 μg/g Hb, respectively, p<0.05] versus controls at 8 weeks. No effects were noted in serum levels of carotenoids and tocopherols and glutathione peroxidase and catalase activities. Green tea extract significantly reduced plasma iron versus baseline (128μg/dL to 92μg/dL, p<0.02), while copper, zinc, and selenium were not affected. These results support the hypothesis that green tea may provide antioxidant protection in the metabolic syndrome.